2007
DOI: 10.1007/s00167-007-0303-2
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting open capsuloplasty for the treatment of anterior shoulder instability: 35-year follow-up of the Du Toit procedure

Abstract: The Du Toit open capsuloplasty for the treatment of anterior shoulder instability is based on the concept of restoring joint stability by recreating the integrity of the anterior glenoid labrum and inferior gleno-humeral ligament using staples. The long-term validity of this procedure for the treatment of anterior shoulder instability was retrospectively assessed by a clinical or telephone interview and radiographic evaluation in 58 patients with an average 35-year follow-up between 1948 and 1974. The range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…1,3,24 The use of 2 screws will probably increase the risk of a hardware complication. 32 We found 1 further study on shoulder stabilization with follow-up exceeding 30 years, 31 which reported a radiologic and clinical follow-up of 58 patients (45 with radiographic examination) operated on with the Du Toit capsuloplasty after mean 35 years, and similar results with respect to patient satisfaction. With the Samilson-Prieto classification, they reported 40% normal shoulders, 49% mild, and 11% moderate or severe arthropathy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…1,3,24 The use of 2 screws will probably increase the risk of a hardware complication. 32 We found 1 further study on shoulder stabilization with follow-up exceeding 30 years, 31 which reported a radiologic and clinical follow-up of 58 patients (45 with radiographic examination) operated on with the Du Toit capsuloplasty after mean 35 years, and similar results with respect to patient satisfaction. With the Samilson-Prieto classification, they reported 40% normal shoulders, 49% mild, and 11% moderate or severe arthropathy.…”
Section: Discussionmentioning
confidence: 85%
“…31 Hovelius and Saeboe 15 showed that mild to severe arthropathy had developed in 55% of the shoulders 25 years after the primary dislocation, even if no redislocation had occurred. Consequently, when different operative methods are evaluated with respect to arthropathy, one also has to consider the natural history of the first-time dislocation, where younger age (22 years) at surgery and primary dislocation have less arthropathy in the long run.…”
mentioning
confidence: 99%
“…The total number of patients included in the various studies was 2600, and varied from 10 14 to 570 22 (Table 2). The mean follow-up time was 16.05 years, ranging from 5 23 to 35 21 years. The average modified CMS was 47.03 (range from 23.0 16 to 76.0 19 ).…”
Section: Study Size and Follow-upmentioning
confidence: 99%
“…Many procedures were performed. The Putti-Platt technique was used in six studies (18.2%), 2,14,24 -27 the Bristow-Latarjet technique was used in seven studies (21.2%), 3,9,15,17,28 -30 the Eden Hybbinette technique was used in six studies (18.2%), 4,25,31 -34 the open Bankart was performed in five studies (15.2%), 6,8,28,35,36 the Trillat technique 15,23 was used in two studies, and arthroscopic Bankart repair, 7 Max Lange 37 and Du Toit, 21 Latarjet Patte 20 and unspecified selective capsular repair 18 were used in one study (3.0%) each. Different techniques (coracoid transfer, open soft tissue reconstruction and arthroscopic stabilization) were used in one study each.…”
Section: Type Of Managementmentioning
confidence: 99%
See 1 more Smart Citation